Real Time Visibility In a Transportation Network of a Complex Supply Chain - Slawomir Wycislak (International Journal of Supply Chain Management, 2021)
The study provides evidences on what are resources and capabilities necessary to achieve real time visibility in a transportation network of a complex supply chain. Strong correlation between subcontracting and untracked shipments suggests resources available within freight forwarders network including systems for storing data on truck and trailer plate numbers, interfaces amongst subcontractors IT systems are of immense importance for achieving real time visibility. On a top of that, digital skills of drivers, privacy concerns are identified as factors affecting data sharing and constraints to achieve real time visibility.